The critical role of fossils in inferring deep‐node phylogenetic relationships and macroevolutionary patterns in Cornales. Issue 8 (24th May 2018) - Atkinson, Brian A.
Abstract : Premise of the Study: The basal asterid order, Cornales, experienced a rapid radiation during the Cretaceous, which has made it difficult to elucidate the early evolution of the order using extant taxa only. Recent paleobotanical studies, however, have begun to shed light on the early diversification of Cornales. Herein, fossils are directly incorporated in phylogenetic and quantitative morphological analyses to reconstruct early cornalean evolution. Methods: A morphological matrix of 77 fruit characters and 58 taxa (24 extinct) was assembled. Parsimony analyses including and excluding fossils were conducted. A fossil inclusive tree was time‐scaled to visualize the timing of the initial cornalean radiation. Disparity analyses were utilized to infer the morphological evolution of cornaleans with drupaceous fruits. Key Results: Fossil inclusive and exclusive parsimony analyses resulted in well‐resolved deep‐node relationships within Cornales. Resolution in the fossil inclusive analysis is substantially higher, revealing a basal grade including Loasaceae, Hydrangeaceae, Hydrostachyaceae, Grubbiaceae, a Hironoia + Amersinia clade, and Curtisiaceae, respectively, that leads to a "core" group containing a clade comprising a Cretaceous grade leading to clade of Nyssaceae, Mastixiaceae, and Davidiaceae that is sister to a Cornaceae+Alangiaceae clade. The time‐scaled tree indicates that the initial cornalean diversification occurred before 89.8 Ma. Disparity analyses suggest the morphological diversity of Cornales peaked during the Paleogene. Conclusions: Phylogenetic analyses clearly demonstrate that novel character mosaics of Cretaceous cornaleans play a critical role in resolving deep‐node relationships within Cornales. The post‐Cretaceous increase of cornalean disparity is associated with a shift in morphospace occupation, which can be explained from ecological and developmental perspectives.